β-Hydroxy β-methylbutyrate (HMB) supplementation during pregnancy and perinatal period in animals studies and possible application in humans - Cieślak, Dominika; Nieradko-Iwanicka, Barbara (Journal of Education, Health and Sport, 2018)
β-Hydroxy β-methylbutyrate (HMB) is a diet supplement known for its positive impact on muscle anabolism, which makes it very popular among amateur sportsmen. Diet enriched with HMB leads to decreased proteolysis in muscle tissue, which is extremely important in the process of muscle regeneration after intensive training. As the number of possible implications of this molecule in medicine is still growing, the aim of this review was to find potential applications of HMB in women and their infants during pregnancy and perinatal period. The HMB usage during pregnancy or shortly after birth is connected with increased muscle anabolism in the infants. Many factors like mTOR signaling pathway, increased activity of GH/IGF-1 axis or elevated blood concentration of some amino acids may be responsible for this effect. Such activity might be potentially helpful for infants born with intrauterine growth retardation (IUGR). Improvement in quality and quantity of colostrum and milk, positive impact on bones and cartilages or immunostimulating effect and deceased enamel roughness, which potentially reduces the risk of caries, are other potential benefits. Although numerous possible positive effects have been postulated, there seems to be insufficient data on safety of long term HMB supplementation, especially in pregnancy and perinatal period. Moreover, there are studies that imply increased peripheral insulin resistance after prolonged supplementation of HMB. HMB usage can be beneficial in numerous health states, also in pregnancy and perinatal period, especially in infants with low birth weight or born preterm, but further investigation is needed to estimate benefits to risk ratio and introduce specific guidelines.